THE USE OF MODERN INTERNET EDUCATIONAL RESOURCES IN TEACHING ENGLISH AT NON-LINGUISTIC UNIVERSITIES - Nykyporets, Svitlana (Collection of scientific papers «ΛΌГOΣ», 2022)
The subject of this article is to study the role and place of information technology in the process of learning English as a foreign language in a technical university. It is noted, that the role of Internet resources in learning English is great, as the Internet provides unique information opportunities and services. Such terms as information technology, linguistics, Internet resources, interactivity, distance and hybrid education were considered. The features and advantages of distance learning using information technology, its role in technical education were analysed.